DESIGN INFLUENCED BY THE EFFECT OF FILTER SELECTION ON THE APPRAISER VARIATION OF THE MEASURING RESULTS OF A 3D OPTICAL MEASURING SYSTEM - Groš, Josip; Mihalić, Tihomir; Medić, Srđan; Šimunić, Nikola (Journal of Energy Technology, 2024)
During the previous decade, 3D optical measuring systems have had an increasing application regarding quality control in different industrial branches where they are commonly used to monitor parts made from sheets, polymers, and castings. The biggest disadvantage of 3D measuring devices is the lack of ISO standards for the calibration of such devices, making it difficult to estimate the quality of the measuring results. The introductory part of the present paper elaborates the working principle of the 3D optical measuring system. In this paper, the free software package GOM inspect is used. When marking the geometric features of the measured metering object, GOM inspects different filters for the selection of the aforementioned features. The experimental part of the paper elaborates the influence of usage of different filters (Gaussian best fit, Chebyshev best-fit, Minimum circumscribed element and Maximum inscribed element) on the measuring results. Reference results are measurements performed on a device with a higher level of accuracy (coordinate measuring device). Afterwards, a comparison of the reference results and measures performed with 3D optical measuring systems using different filters was made.